Two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material and preparation method and application thereof
By adopting two-dimensional high-entropy ceramic nanosheets/polymer composite dielectric film materials, nanosheets with "core-shell" structures are prepared by using the "sol-gel method" and the laminar casting method, the problem that existing dielectric energy storage materials are difficult to take into account high dielectric breakdown strength and high energy storage density, and efficient dielectric energy storage performance is achieved.
Patent Information
- Application Number
- CN202411820427.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult for existing dielectric energy storage materials to take into account both high dielectric breakdown strength and high energy storage density.
Two-dimensional high-entropy ceramic nanosheets/polymer composite dielectric film material were used to prepare two-dimensional high-entropy ceramic nanosheets with "core-shell" structure by the "sol-gel method", and composite dielectric film material was prepared by the "sol-gel method", and composite dielectric film material was composited with the PVDF-PMMA organic polymer material.
It achieves a balance between high dielectric breakdown strength and high energy storage density, significantly improving the dielectric energy storage performance of the material, and is suitable for high-performance capacitors and electrostatic energy storage materials.
Smart Images

Figure CN119639050A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material and a preparation method and application thereof. Background Art
[0002] With the development of information technology, miniaturization and lightweight are the main trends in the development of electronic components in the field of electronics and microelectronics. Capacitors have received extensive attention as basic components. In new fields such as electric vehicles and laser weapons, capacitors can be used as energy storage devices and power devices due to their rapid discharge. Therefore, the key materials (dielectric materials) for the preparation of such capacitors are required to have excellent properties such as high dielectric constant, high polarization value, low dielectric loss and high electric field strength.
[0003] Common energy storage capacitor materials include polymer materials and electronic ceramics. Compared with electronic ceramics, polymers have higher Young's modulus and higher breakdown field strength, and their breakdown field strength can reach more than 400MV / m. In addition, polymer materials are widely used in dielectric materials due to their advantages such as easy processing, good flexibility, light weight, and the ability to be made into large-area films. However, the dielectric constant of polymer materials is relatively low, resulting in low energy storage density. To increase the dielectric constant of dielectrics, an effective way is to add inorganic particles with high dielectric constant to fluorinated polymers (such as polyvinylidene fluoride PVDF) to obtain polymer composites with high breakdown electric field and high dielectric constant. Among them, filler morphology is an important factor affecting the energy storage performance of composite materials. Due to the special anisotropic morphology and properties of two-dimensional (2D) materials, they show great potential in improving energy storage performance. In particular, nanosheets have high mechanical strength, and their large lateral dimensions can effectively transfer in-plane loads. Therefore, at low content, nanosheets can significantly improve the mechanical properties of polymer composite dielectrics. Secondly, the dispersed nanosheets produce a spatial blocking effect inside the medium, forcing the breakdown path to expand around them. Their larger lateral size can effectively increase the length and difficulty of the breakdown path extension, thereby improving the breakdown field strength of the nanocomposite medium. In addition, the nanosheets have a large specific surface area, and a large number of filler-polymer interfaces can be introduced to improve polarization. Some researchers have used lanthanum-modified lead zirconate titanate (PLZT) (nanoparticles, nanowires, and nanosheets) with different morphologies as fillers to obtain high breakdown field strength E in polymer-based nanocomposites containing 2D PLZT nanosheets. b (430MV / m) and high energy storage density U e (13.9J / cm 3 ). It can be seen that the existing methods only improve the energy storage performance of materials by optimizing the filler morphology from nanoparticles to nanosheets, and have not yet involved improving the energy storage performance of materials by optimizing and regulating the filler composition and structure.
[0004] High entropy materials exhibit excellent dielectric properties due to their inherent cocktail effect, phase stability, atomic disordered lattice distortion and slow diffusion kinetics. 0.85 Nd 0.1 Sm 0.05 ) 1-x Ba x (Fe 1-x Ti x )O3 high entropy ceramics, the increase in configurational entropy breaks the long-range order, the residual polarization decreases, and U e The energy storage density U of the ceramic under a low electric field of 250 kV / cm e Up to 4.9J / cm 3 Other studies have shown that local inhomogeneity increases with increasing entropy, and the relaxation characteristics are modulated accordingly. 4-x La x / 4 Pr x / 4 Nd x / 4 Sm x / 4 )Ti3O 12 178.1 J / cm was obtained in the film 3 High energy storage density U e and a discharge efficiency η of 80.5%. Yang et al. found that adjusting the atomic configuration entropy to introduce good and stable microstructural features such as lattice distortion nanograins and disordered amorphous phases improved E b , reducing the polarization switch hysteresis, thereby synergistically improving the energy storage performance. 3.25 La 0.75 )(Ti 3-3x Zr x Hf x Sn x ) 12 182 J / cm was obtained in the film 3 Ultra-high energy storage density U e Therefore, high entropy engineering has important research significance in the field of inorganic dielectric ceramics and inorganic dielectric films. However, in order to improve the mechanical properties of high entropy dielectric materials and broaden their application areas, more attention should be paid to polymer-based dielectric energy storage films filled with high entropy ceramic powders. For example, researchers obtained (Bi 3.25 La 0.75 )(Ti 3-3x Zr x Hf x Sn x ) 12 High-entropy nanofibers with a stable linear pyrocrystalline phase and high electric displacement; energy storage density U of composites embedded with high-entropy fillers e6.46 J / cm 3 , is polyetherimide (PEI) (2.92J / cm 3 ). Some researchers have also used electrospinning to prepare (Eu 0.2 Bi 0.2 Y 0.2 La 0.2 Cr 0.2 )2O3 high entropy nanofibers and composite them with P(VDF-HFP) / polymethyl methacrylate (PMMA). The enhancement of lattice entropy leads to local polycrystalline distortion, which restricts the movement of long polymer chains, reduces dielectric loss, and improves the breakdown field strength E of the composite material. b , at 509.4kV / mm, the energy storage density U e Reach 15.13J / cm 3 . In summary, high entropy powder materials are important dielectric energy storage materials, and their preparation methods mainly include solid-phase method, electrospinning method and hydrothermal method. The solid-phase method requires very high temperature to prepare high entropy powders, and the obtained high entropy powders are large in size and difficult to control in morphology. The electrospinning method requires expensive electrospinning equipment to prepare high entropy powders, and it may need to be carried out in highly corrosive or highly toxic solvents. Organic solvents are expensive, difficult to recycle, and easy to cause environmental pollution. The morphology of the high entropy powder materials prepared so far is mainly nanoparticles and nanofibers; however, high entropy nanoparticles and high entropy nanofibers are easy to agglomerate in the polymer matrix, which is not conducive to improving the breakdown field strength E b .
[0005] In summary, the preparation of two-dimensional high-entropy ceramic nanosheets is a very difficult and critical problem that needs to be solved urgently. How to achieve the controllable preparation of two-dimensional high-entropy ceramic nanosheets so that they can simultaneously take into account high dielectric breakdown strength and high energy storage density in dielectric energy storage, thereby improving the dielectric energy storage performance of the material is a hot topic of research at this stage. Summary of the invention
[0006] The purpose of the present invention is to provide a two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material and its preparation method and application. First, a two-dimensional high entropy ceramic nanosheet is prepared, and then it is composited with organic matter to prepare a dielectric film material. This dielectric film material is used in energy storage capacitors to solve the technical problem that the high dielectric breakdown strength and high energy storage density of existing dielectric energy storage materials cannot be taken into account at the same time, greatly improving the dielectric energy storage of the material.
[0007] The solution of the present invention to solve the above technical problems is as follows:
[0008] A two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material, comprising an intermediate layer of a KNN@LNBCT / PVDF-PMMA composite material and upper and lower layers of a PVDF-PMMA organic polymer material; in the intermediate layer, the mass ratio of KNN to PVDF-PMMA is 2.28% to 16.01%, and the mass ratio of LNBCT to PVDF-PMMA is 0.61% to 4.32%.
[0009] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material comprises the following steps:
[0010] S1. Preparation of two-dimensional nanosheet KNN
[0011] Two-dimensional nanosheets KNN were prepared by hydrothermal method using niobium pentoxide, sodium hydroxide, potassium hydroxide and ethylene glycol as raw materials;
[0012] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0013] A mixed solution containing barium, calcium, lanthanum, sodium and titanium ions is prepared using lanthanum acetate, sodium nitrate, barium nitrate, calcium nitrate, tetrabutyl titanate, anhydrous ethanol and acetic acid as raw materials, and then the two-dimensional nanosheet KNN and the mixed solution are mixed according to the mass ratio to prepare a two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure through a "sol-gel method";
[0014] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0015] Using two-dimensional high-entropy ceramic nanosheets KNN@LNBCT, PVDF and PMMA as raw materials, the upper and lower layers containing PVDF-PMMA organic polymer materials and the middle layer containing KNN@LNBCT / PVDF-PMMA composite materials were prepared respectively. The two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA was prepared by layer-by-layer casting method.
[0016] It is further defined that in step S1, the molar ratio of niobium pentoxide, sodium hydroxide and potassium hydroxide is 1:1:3.5.
[0017] It is further defined that the specific process of preparing the two-dimensional high entropy ceramic nanosheet KNN@LNBCT in step S2 is:
[0018] S21, dissolving tetrabutyl titanate in a mixture of ethanol and acetic acid, and then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, stirring evenly to obtain a mixed solution containing barium, calcium, lanthanum, sodium and titanium ions; the molar ratio of lanthanum, sodium, barium, calcium and titanium is 0.25:0.25:0.25:0.25:1;
[0019] S22, adding the two-dimensional nanosheet KNN obtained in step S1 to the mixed solution obtained in step S22, and mixing them thoroughly to obtain a turbid solution; and adjusting the pH to 6-7 under stirring conditions to obtain a precursor sol containing KNN@LNBCT;
[0020] S23, gelling the precursor sol containing KNN@LNBCT to obtain a gel, and then drying and calcining to obtain a two-dimensional high entropy ceramic nanosheet KNN@LNBCT.
[0021] It is further defined that in step S21, ethanol-acetic acid is prepared by mixing anhydrous ethanol and acetic acid in equal volumes; the stirring time is 0.5h to 2h;
[0022] In step S22, the stirring time is 0.5h to 2h;
[0023] In the step S23, gelation is performed by heating in a water bath at 50°C to 90°C; drying is performed at 50°C to 90°C for 10 hours to 24 hours, and then calcining is performed at 500°C to 900°C for 1 hour to 3 hours.
[0024] It is further defined that the specific process of preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material in step S3 is:
[0025] S31, dispersing PVDF and PMMA in DMF solvent, stirring evenly to obtain suspension A, i.e., upper and lower layers containing PVDF-PMMA organic polymer material;
[0026] S32, ultrasonically dispersing the two-dimensional high entropy ceramic nanosheets KNN@LNBCT in the suspension A, and stirring to obtain a suspension B, which is an intermediate layer containing the KNN@LNBCT / PVDF-PMMA composite material;
[0027] S33. Evenly coat suspension A on clean glass and dry it; then coat suspension B and suspension A on suspension A in sequence and dry them; remove the solvent and quench it to obtain the two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA.
[0028] It is further defined that in step S31, the mass volume ratio of PVDF, PMMA and DMF is 0.2 g:0.05 g:2.0 mL.
[0029] Application of a two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material in high dielectric energy storage capacitors.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention comprises a two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material composed of a blended polymer and a high-entropy ceramic nanosheet KNN@LNBCT of a "core-shell" structure dispersed in the polymer. This dielectric thin film material has few defects, high breakdown field strength, high energy storage density and high charge and discharge efficiency in a high temperature environment, and is a material that can be used for capacitors and high-power electrostatic energy storage.
[0032] 2. The present invention synthesizes and prepares two-dimensional high-entropy ceramic nanosheets through the "sol-gel method", and then adopts the casting method to prepare the composite dielectric thin film material. The preparation method is simple and easy to realize industrialization.
[0033] 3. During the preparation process of the present invention, by optimizing the raw material ratio, the two-dimensional high-entropy ceramic nanosheets can simultaneously have the high breakdown field strength and energy storage density of two-dimensional nanosheets and high-entropy materials, thereby greatly improving the dielectric energy storage properties of the composite dielectric film material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the XRD pattern of sample #P0 in Example 1;
[0035] Figure 2 TEM image, HAADF image and energy spectrum of sample #P0 in Example 1;
[0036] Figure 3 XRD diagrams of samples #F1, #F2, #F3 and #F4 in Examples 1 to 4;
[0037] Figure 4 The cross-sectional SEM photos of the #F1 sample, the #F2 sample, the #F3 sample and the #F4 sample in Examples 1 to 4;
[0038] Figure 5 The Weibull distribution and content dependence of the Weibull breakdown strength of the #F1 sample, the #F2 sample, the #F3 sample and the #F4 sample in Examples 1 to 4;
[0039] Figure 6 The dielectric properties of samples #F1, #F2, #F3 and #F4 in Examples 1 to 4;
[0040] Figure 7 The energy storage performance of the #F1 sample, the #F2 sample, the #F3 sample and the #F4 sample in Examples 1 to 4;
[0041] Figure 8 XRD diagrams of samples #P1, #P2, #P3, #P4 and #P5 in Examples 5 to 9;
[0042] Fig. 9 SEM photos of samples #P1, #P2, #P3, #P4 and #P5 in Examples 5 to 9;
[0043] Fig.10 XRD diagrams of samples #F5, #F6, #F7, #F8 and #F9 in Examples 5 to 9;
[0044] Fig.11 The cross-sectional SEM photos of samples #F5, #F6, #F7, #F8 and #F9 in Examples 5 to 9;
[0045] Fig.12 The Weibull distribution and content dependence of the Weibull breakdown strength of samples #F5, #F6, #F7, #F8 and #F9 in Examples 5 to 9;
[0046] Fig.13 The dielectric properties of samples #F5, #F6, #F7, #F8 and #F9 in Examples 5 to 9;
[0047] Fig.14 The energy storage performance of samples #F5, #F6, #F7, #F8 and #F9 in Examples 5 to 9. DETAILED DESCRIPTION
[0048] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] It should be noted that, unless otherwise specified, the chemicals, reagents or solvents used in the following examples are all conventional commercially available products in the art.
[0050] It should be noted that, unless otherwise specified, the operating means or operating conditions used in the following examples are all conventional operating means or operating conditions. For example, unless otherwise specified, the temperature is room temperature and the pressure is normal pressure.
[0051] In the following examples, PVDF refers to polyvinylidene fluoride, PMMA refers to polymethyl methacrylate, and DMF refers to N,N-dimethylformamide.
[0052] Example 1
[0053] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0054] S1. Preparation of two-dimensional nanosheet KNN
[0055] Niobium pentoxide, potassium hydroxide and sodium hydroxide are mixed in a molar ratio of 1:1:3.5, the solvent is 25 mL of ethylene glycol, and magnetic stirring is performed for 6 hours to fully mix; the mixture is then transferred to a high-pressure reactor, reacted at 200°C for 12 hours, cooled to room temperature, washed with deionized water and ethanol, and vacuum dried at 60°C for 12 hours to obtain a niobate precursor; the niobate precursor is then placed in a crucible and calcined at a temperature of 600°C for 2 hours to obtain a two-dimensional nanosheet, denoted as KNN, also known as two-dimensional nanosheet KNN.
[0056] In this step, during the calcination process, a solid phase reaction occurs, converting the niobate precursor into potassium sodium niobate.
[0057] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0058] In this step, the specific steps of preparing the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure by the "sol-gel method" are as follows:
[0059] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1;
[0060] S23, adding 0.2 g of the two-dimensional nanosheet KNN obtained in step S1 to the mixed solution obtained in step S21, stirring sufficiently to obtain a turbid solution; stirring for another 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a precursor sol containing KNN@LNBCT;
[0061] S25. The precursor sol containing KNN@LNBCT was heated in a water bath at 80°C to obtain a gel; after vacuum drying at 80°C for 24 hours, it was calcined at 700°C for 2 hours to obtain a two-dimensional high-entropy ceramic nano KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN was 27%, which was recorded as #P0 sample.
[0062] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0063] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P0 sample), PVDF and PMMA as raw materials, and prepares two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film materials by layer-by-layer casting method, which is recorded as KNN@LNBCT / PVDF-PMMA.
[0064] 0.2g PVDF and 0.05 g PMMA was dispersed in 2.0 mL DMF and stirred to obtain suspension A, which is the upper and lower layers containing PVDF-PMMA organic polymer materials, and is used to prepare composite dielectric thin film materials. Two-dimensional high entropy ceramic nanosheets (#P0 sample) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which is the middle layer containing KNN@LNBCT / PVDF-PMMA composite materials, and is used to prepare composite dielectric thin film materials.
[0065] In this embodiment, the mass ratio of the KNN material to the PVDF-PMMA in the middle layer is 2.28%, and the mass ratio of the LNBCT high entropy material to the PVDF-PMMA is 0.61%.
[0066] The preparation process of composite dielectric thin film materials is as follows:
[0067] First, 70 μL of suspension A was evenly coated on a clean glass and dried to obtain a bottom layer (or lower layer) containing suspension A. Similarly, 70 μL of suspension B (middle layer) and 70 μL of suspension A (upper layer) were coated on the bottom layer surface from bottom to top, dried at 60 ° C for 12 h, and the solvent was removed. Finally, the obtained film was heated at 200 ° C for 10 min and immediately quenched in ice water to obtain a two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA, which was recorded as sample #F1.
[0068] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0069] In this embodiment, the microstructure and dielectric properties of the #P0 sample and the #F1 sample are studied.
[0070] The XRD pattern, TEM pattern, HAADF pattern and energy spectrum of the #P0 sample are shown in Figure 1 and Figure 2 The XRD pattern, cross-sectional SEM image, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F1 sample are shown in Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 .
[0071] Example 2
[0072] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0073] S1. Preparation of two-dimensional nanosheet KNN
[0074] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 1.
[0075] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0076] In this step, a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure is prepared by a "sol-gel method", and the specific process is the same as that in Example 1.
[0077] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0078] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material is referred to Example 1, and the difference from Example 1 is that:
[0079] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 6.85%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 1.85%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is recorded as sample #F2.
[0080] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0081] In this example, the microstructure and dielectric properties of sample #F2 were studied.
[0082] The XRD pattern, cross-sectional SEM photo, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F2 sample are shown in Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 .
[0083] Example 3
[0084] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0085] S1. Preparation of two-dimensional nanosheet KNN
[0086] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 1.
[0087] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0088] In this step, a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure is prepared by a "sol-gel method", and the specific process is the same as that in Example 1.
[0089] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0090] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material is referred to Example 1, and the difference from Example 1 is that:
[0091] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 11.43%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 3.08%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is denoted as sample #F3.
[0092] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0093] In this example, the microstructure and dielectric properties of sample #F3 were studied.
[0094] The XRD pattern, cross-sectional SEM photo, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F3 sample are shown in Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 .
[0095] Example 4
[0096] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0097] S1. Preparation of two-dimensional nanosheet KNN
[0098] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 1.
[0099] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0100] In this step, the specific process of preparing the two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure by the "sol-gel method" is the same as that in Example 1.
[0101] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0102] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material is referred to Example 1, and the difference from Example 1 is that:
[0103] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 16.01%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 4.32%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is recorded as sample #F4.
[0104] The two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material, KNN@LNBCT / PVDF-PMMA, prepared in this embodiment has a "core-shell" structure.
[0105] In this example, the microstructure and dielectric properties of sample #F4 were studied.
[0106] The XRD pattern, cross-sectional SEM photo, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F4 sample are shown in Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 .
[0107] Example 5
[0108] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0109] S1. Preparation of two-dimensional nanosheet KNN
[0110] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 2.
[0111] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0112] In this step, the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a core-shell structure is prepared by the sol-gel method. The specific steps are as follows:
[0113] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium is 0.25:0.25:0.25:0.25:1;
[0114] S22, adding 0.2 g of the two-dimensional nanosheet KNN obtained in step S1 to the mixed solution obtained in step S21, stirring sufficiently to obtain a turbid solution; stirring for another 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a precursor sol containing KNN@LNBCT;
[0115] S23. The precursor sol containing KNN@LNBCT was heated in a water bath at 80°C to obtain a gel; after vacuum drying at 80°C for 24 hours, it was calcined at 700°C for 2 hours to obtain a two-dimensional high entropy nanosheet KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN was 10%, which was recorded as sample #P1.
[0116] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0117] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P1 sample), PVDF and PMMA as raw materials to prepare two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA by layer-by-layer casting method.
[0118] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is referred to Example 2, and the difference from Example 2 is that:
[0119] The two-dimensional high entropy ceramic nanosheets (sample #P1) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which contained the intermediate layer of the KNN@LNBCT / PVDF-PMMA composite material and was used to prepare the composite dielectric thin film material.
[0120] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 13.12%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 0.13%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is denoted as sample #F5.
[0121] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0122] In this embodiment, the microstructure and dielectric properties of sample #P1 and sample #F5 are studied.
[0123] The XRD and SEM images of the #P1 sample are shown in Figure 8 and Fig. 9 The XRD pattern, cross-sectional SEM image, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F5 sample are shown in Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 .
[0124] Example 6
[0125] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0126] S1. Preparation of two-dimensional nanosheet KNN
[0127] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 2.
[0128] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0129] In this step, the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a core-shell structure is prepared by the sol-gel method. The specific steps are as follows:
[0130] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1;
[0131] S22, adding 0.2 g of KNN two-dimensional nanosheet powder obtained in step S1 to the mixed solution obtained in step S21, stirring sufficiently to obtain a turbid solution; stirring for another 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a KNN@LNBCT precursor sol;
[0132] S23. The precursor sol containing KNN@LNBCT was heated in a water bath at 80°C to obtain a gel; after vacuum drying at 80°C for 24 hours, it was calcined at 700°C for 2 hours to obtain a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN was 15%, which was recorded as sample #P2.
[0133] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0134] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P2 sample), PVDF and PMMA as raw materials to prepare two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA by layer-by-layer casting method.
[0135] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is referred to Example 2, and the difference from Example 2 is that:
[0136] The two-dimensional high entropy ceramic nanosheets (sample #P2) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which contained the intermediate layer of the KNN@LNBCT / PVDF-PMMA composite material and was used to prepare the composite dielectric thin film material.
[0137] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 12.62%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 1.89%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is recorded as sample #F6.
[0138] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0139] In this embodiment, the microstructure and dielectric properties of sample #P2 and sample #F6 are studied.
[0140] The XRD and SEM images of the #P2 sample are shown in Figure 8 and Fig. 9The XRD pattern, cross-sectional SEM image, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F5 sample are shown in Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 .
[0141] Example 7
[0142] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0143] S1. Preparation of two-dimensional nanosheet KNN
[0144] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 2.
[0145] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0146] In this step, the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a core-shell structure is prepared by the sol-gel method. The specific steps are as follows:
[0147] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1;
[0148] S22, adding 0.2 g of KNN nanosheet powder obtained in step S1 to the mixed solution obtained in step S21, stirring thoroughly to obtain a turbid solution; stirring for 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a KNN@LNBCT precursor sol;
[0149] S23. The KNN@LNBCT sol was heated in a water bath at 80°C to obtain a gel, and then vacuum dried at 80°C for 24 hours and then calcined at 700°C for 2 hours to obtain a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN was 20%, which was recorded as sample #P3.
[0150] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0151] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P3 sample), PVDF and PMMA as raw materials to prepare two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA by layer-by-layer casting method.
[0152] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is referred to Example 2, and the difference from Example 2 is that:
[0153] The two-dimensional high entropy ceramic nanosheets (sample #P3) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which contained the intermediate layer of the KNN@LNBCT / PVDF-PMMA composite material and was used to prepare the composite dielectric thin film material.
[0154] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 12.09%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 2.41%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is recorded as sample #F7.
[0155] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0156] In this embodiment, the microstructure and dielectric properties of sample #P3 and sample #F7 are studied.
[0157] The XRD and SEM images of the #P3 sample are shown in Figure 8 and Fig. 9 The XRD pattern, cross-sectional SEM image, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F7 sample are shown in Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 .
[0158] Example 8
[0159] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0160] S1. Preparation of two-dimensional nanosheet KNN
[0161] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 2.
[0162] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0163] In this step, the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a core-shell structure is prepared by the sol-gel method. The specific steps are as follows:
[0164] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1;
[0165] S22, adding 0.2 g of KNN nanosheet powder obtained in step S1 to the mixed solution obtained in step S21, stirring sufficiently to obtain a turbid solution; stirring for another 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a KNN@LNBCT precursor sol;
[0166] S23. The precursor sol containing KNN@LNBCT is heated in a water bath at 80°C to obtain a gel; after vacuum drying at 80°C for 24 hours, it is calcined at 700°C for 2 hours to obtain a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN is 25%, which is recorded as sample #P4.
[0167] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0168] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P4 sample), PVDF and PMMA as raw materials to prepare two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMM by layer-by-layer casting method.
[0169] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMM is based on Example 2, and the difference from Example 2 is that:
[0170] The two-dimensional high entropy ceramic nanosheets (sample #P4) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which contained the intermediate layer of the KNN@LNBCT / PVDF-PMMA composite material and was used to prepare the composite dielectric thin film material.
[0171] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 11.61%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 2.90%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is denoted as sample #F8.
[0172] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0173] In this embodiment, the microstructure and dielectric properties of sample #P4 and sample #F8 are studied.
[0174] The XRD and SEM images of the #P4 sample are shown in Figure 8 and Fig. 9 The XRD pattern, cross-sectional SEM image, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F8 sample are shown in Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 .
[0175] Example 9
[0176] The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material provided in this embodiment comprises the following steps:
[0177] S1. Preparation of two-dimensional nanosheet KNN
[0178] In this step, the preparation of the two-dimensional nanosheet KNN is the same as that in Example 2.
[0179] S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT
[0180] In this step, the two-dimensional high entropy ceramic nanosheet KNN@LNBCT with a core-shell structure is prepared by the sol-gel method. The specific steps are as follows:
[0181] S21, dissolving tetrabutyl titanate in a mixture of 5.0 mL of ethanol and 5.0 mL of acetic acid; then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, and stirring for 1 hour to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1;
[0182] S22, adding 0.2 g of KNN nanosheet powder obtained in step S1 to the mixed solution obtained in step S21, stirring sufficiently to obtain a turbid solution; stirring for another 30 min and adding ammonia water to adjust the pH to 6-7 to obtain a KNN@LNBCT precursor sol;
[0183] S23. The precursor sol containing KNN@LNBCT was heated in a water bath at 80°C to obtain a gel; after vacuum drying at 80°C for 24 hours, it was calcined at 700°C for 2 hours to obtain a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure in which the mass ratio of LNBCT to KNN was 30%, which was recorded as sample #P5.
[0184] S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials
[0185] This step mainly uses two-dimensional high-entropy ceramic nanosheets (#P5 sample), PVDF and PMMA as raw materials to prepare two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA by layer-by-layer casting method.
[0186] In this step, the preparation process of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is referred to Example 2, and the difference from Example 2 is that:
[0187] The two-dimensional high entropy ceramic nanosheets (sample #P5) were ultrasonically dispersed in suspension A and stirred to obtain suspension B, which contained the intermediate layer of the KNN@LNBCT / PVDF-PMMA composite material and was used to prepare the composite dielectric thin film material.
[0188] In the middle layer of this step, the mass ratio of KNN material to PVDF-PMMA is 11.16%, and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 3.35%. The prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is denoted as sample #F9.
[0189] The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA prepared in this embodiment has a "core-shell" structure.
[0190] In this embodiment, the microstructure and dielectric properties of the #P5 sample and the #F9 sample were studied.
[0191] The XRD and SEM images of the #P5 sample are shown in Figure 8 and Fig. 9The XRD pattern, cross-sectional SEM photo, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties, and energy storage properties of the #F9 sample are shown in Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 .
[0192] In the above embodiment of the present invention, the parameters for preparing the two-dimensional nanosheets KNN in step S1 can also be arbitrarily selected within the following ranges: stirring time is 1 to 7 hours; reaction temperature is 180 to 220°C, and reaction time is 10 to 12 hours; drying temperature is 50 to 90°C, and drying time is 10 to 24 hours; calcination temperature is 500 to 900°C, and calcination time is 1 to 3 hours.
[0193] In the above embodiment of the present invention, the preparation parameters in step S2 can also be arbitrarily selected within the following ranges: in step S21, the stirring time is 0.5 to 2 hours; in step S22, the stirring time is 0.5 to 2 hours; in step S23, gelation is performed by heating in a water bath at 50 to 90°C; drying at 50 to 90°C for 10 to 24 hours, and then calcining at 500 to 900°C for 1 to 3 hours.
[0194] In the above embodiment of the present invention, the preparation parameters in step S33 can also be arbitrarily selected within the following ranges: drying at 50-80° C. for 10-14 hours; heating at 180-220° C. for 5-20 minutes and then immediately quenching in ice water.
[0195] In order to illustrate the technical advantages of the two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA of the present invention, its physical and chemical properties were experimentally verified. The specific experiments are as follows.
[0196] In the experimental verification, in order to highlight the performance advantages of the two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA of the present invention, the following comparative example was designed for comparison.
[0197] Comparative Example 1
[0198] In this comparative example, the preparation steps of PVDF-PMMA high entropy dielectric energy storage film material are as follows:
[0199] PVDF and PMMA were used as raw materials and PVDF-PMMA dielectric energy storage film materials were prepared by layer-by-layer casting method.
[0200] 0.2g PVDF and 0.05 g PMMA was dispersed in 2.0 mL of DMF and stirred evenly to obtain a suspension, which was used to prepare the nanocomposite film.
[0201] 70 μL of suspension A was evenly coated on a clean glass and dried at 60°C for 12 hours to remove the solvent. Finally, the film was heated at 200°C for 10 minutes and then immediately placed in ice water for quenching to obtain a PVDF-PMMA high entropy dielectric energy storage film material, which was recorded as Comparative Example 1 sample.
[0202] In this comparative example, the microstructure and dielectric properties of the sample of comparative example 1 were studied.
[0203] The XRD pattern, Weibull distribution and content dependence of Weibull breakdown strength, dielectric properties and energy storage performance of the sample of Comparative Example 1 are shown in Table 1. Figure 3 , Figure 5 , Figure 6 and Figure 7 .
[0204] The performance study results of the samples in the above examples and comparative examples are as follows.
[0205] Test 1
[0206] The #P0 sample prepared in Example 1 was characterized by bulk XRD analysis.
[0207] The test process is: the phase composition of the ceramic sheet is directly detected by powder X-ray diffraction (XRD). The test conditions are: using Cu-Kα target as the ray source, the test tube voltage is 40kV, the test tube current is 40mA, the scanning step is 0.02°, the scanning rate is 0.05° / s, and the Jade software is used for analysis. The results are as follows: Figure 1 shown.
[0208] pass Figure 1 It can be seen that the diffraction peaks of the two-dimensional high entropy ceramic nanosheets KNN@LNBCT NSs are similar to those of KNbO3 (KN, PDF#32-0822, green), Na 0.5 La 0.5 TiO3 (LNTO, PDF#39-0065, orange), CaTiO3 (CTO, PDF#42-0423, blue), LaTiO3 (LTO, PDF#49-0426, pink) and BaTiO3 (BTO, PDF#31-0174, red) are compared. The two-dimensional high entropy ceramic nanosheet KNN@LNBCT NSs is a single-phase perovskite structure. This indicates that multiple cations at the A site successfully enter the lattice to form a uniform solid solution. In addition, the diffraction peaks of the samples are compared with those of BTO (PDF#31-0174). The shift of the diffraction peaks to higher angles means that the lattice parameters are squeezed, and the lattice contraction is caused by the internal stress between different ions.
[0209] Test 2
[0210] The #P0 sample prepared in Example 1 was dispersed in the solvent ethanol, and after dilution, a small amount of liquid was dripped onto the copper mesh using a pipette, and then dried for about 1 hour. An energy dispersive X-ray spectrometer (EDS) was used to perform an EDS surface element scan, and the results were as follows: Figure 2 shown.
[0211] See also Figure 2 The two-dimensional high-entropy ceramic nanosheet KNN@LNBCT has a flaky morphology with a width of 1-3μm and a thickness of 10-50nm, and has a high aspect ratio. Element mapping proves that the element distribution map of KNN@LNBCT contains not only K, Na, Nb, O, but also La, Ba, Ca and Ti elements, which are evenly distributed in various positions of the sample. TEM and EDS results show that the edges of the nanosheets with a "core-shell" structure have obvious light and dark contrast, and the thickness of the coating layer is about 11nm. Elements such as K, Nb, Na and O are evenly distributed in various positions of the sample. The two-dimensional high-entropy ceramic nanosheet KNN@LNBCT obtained by the present invention satisfies the "core-shell" structure.
[0212] Test 3
[0213] The #F1 sample, #F2 sample, #F3 sample and #F4 sample prepared in Examples 1 to 4 and the PVDF-PMMA high entropy dielectric energy storage thin film material prepared in Comparative Example 1 were compared using bulk XRD analysis.
[0214] pass Figure 3 It can be seen that the KNN@LNBCT / PVDF-PMMA two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials prepared in Examples 1 to 4 contain strong perovskite phase diffraction peaks in addition to the PVDF-specific phase structure diffraction peaks.
[0215] The diffraction peaks at 2θ = 22° and 31.6° belong to the (110) and (111) crystal planes of KNN, respectively. With the increase of KNN@LNBCT content in the film, the intensity of the diffraction peaks gradually increases. (111) / A (110) As the content of KNN@LNBCT increases, A (111) / A (110) The value gradually increases, which may be related to the texture of KNN@LNBCT along the (111) crystal plane in the film.
[0216] Test 4
[0217] The cross sections of the #F1 sample, #F2 sample, #F3 sample and #F4 sample prepared in Examples 1 to 4 of the present invention were observed by SEM. The results are as follows: Figure 4 shown.
[0218] See also Figure 4 , the multilayer nanocomposite film is about 10μm thick, dense and flat, with no obvious defects. Further magnification shows that several two-dimensional high-entropy ceramic nanosheets KNN@LNBCT with a lateral size of more than 2μm can be identified on the cross-section of all samples, which are well dispersed and tightly surrounded by the polymer matrix. This shows that the two-dimensional high-entropy ceramic nanosheets KNN@LNBCT have good compatibility with the polymer matrix. Most of the nanosheets are oriented parallel to the plane direction of the film. The orientation distribution of the two-dimensional high-entropy ceramic nanosheets KNN@LNBCT can produce an interface barrier effect, which is beneficial to improve the breakdown strength of the nanocomposite film.
[0219] Test 5
[0220] The #F1 sample, #F2 sample, #F3 sample and #F4 sample prepared in Examples 1 to 4 of the present invention and the PVDF-PMMA high entropy dielectric energy storage film material prepared in Comparative Example 1 were respectively subjected to ion sputtering to prepare gold electrodes with a diameter of 2 mm on both sides thereof, and their dielectric properties and energy storage properties were tested by conventional detection means. The specific results are as follows: Figure 5 to Figure 7 shown.
[0221] pass Figure 5 , Figure 6 and Figure 7 It can be seen that compared with the PVDF-PMMA high-entropy dielectric energy storage film material, the two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA prepared by the present invention has higher dielectric properties and energy storage density. It shows that the two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure can significantly improve the dielectric properties and energy storage density of the PVDF-PMMA film. For Example 3, when the content of KNN@LNBCT with a "core-shell" structure is 5%, the dielectric constant of the two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA is 13.9, the breakdown field strength is 549MV / m, and the maximum energy storage density is 22.18J / cm 3 And the energy storage efficiency is 69.8%.
[0222] Test 6
[0223] XRD phase analysis was performed on the #P1 sample, #P2 sample, #P3 sample, #P4 sample and #P5 sample prepared in Examples 5 to 9 of the present invention. The results are as follows: Figure 8 shown.
[0224] Depend on Figure 8It can be seen that the #P1 sample, the #P2 sample, the #P3 sample, the #P4 sample and the #P5 sample in Examples 5 to 9 have very strong perovskite phase diffraction peaks.
[0225] Test 7
[0226] SEM observation was performed on the #P1 sample, #P2 sample, #P3 sample, #P4 sample and #P5 sample prepared in Examples 5 to 9 of the present invention. The results are as follows: Fig. 9 shown.
[0227] Depend on Fig. 9 It can be seen that the two-dimensional high entropy ceramic nanosheets #P1, #P2, #P3, #P4 and #P5 in Examples 5 to 9 all present a two-dimensional sheet-like morphology and good monodispersity, indicating that the coating process did not destroy the morphology of the core material KNN nanosheets, nor did it produce a large amount of agglomeration. After coating, the nanosheets became thicker and the surface became rougher. As the coating amount continued to increase, the thickness of the KNN@LNBCT nanosheets gradually became thicker. The preparation of KNN@LNBCT nanosheets with different LNBCT coating amounts was achieved.
[0228] Test 8
[0229] Take the #F5 sample, #F6 sample, #F7 sample, #F8 sample and #F9 sample in Examples 5 to 9 and perform XRD analysis respectively. The results are as follows: Fig.10 shown.
[0230] pass Fig.10 It can be seen that in Examples 5 to 9, samples #F5, #F6, #F7, #F8 and #F9 all contain strong perovskite phase diffraction peaks in addition to the PVDF-specific phase structure diffraction peaks. This indicates that KNN@LNBCT and PVDF-PMMA with a "core-shell" structure both exist and do not affect each other, thereby maintaining their respective dielectric constants.
[0231] Test 9
[0232] The cross sections of the #F5 sample, #F6 sample, #F7 sample, #F8 sample and #F9 sample prepared in Examples 5 to 9 of the present invention were observed by SEM. The results are as follows: Fig.11 shown.
[0233] See also Fig.11 The thickness of the multilayer nanocomposite film is about 10 μm, with no obvious defects. The two-dimensional high-entropy ceramic nanosheets KNN@LNBCT with a "core-shell" structure are well dispersed in PVDF-PMMA and are tightly wrapped by the surrounding polymer matrix without holes, indicating that the film is dense. The two-dimensional high-entropy ceramic nanosheets KNN@LNBCT are oriented parallel to the plane direction of the film.
[0234] Test 10
[0235] Take the #F5 sample, #F6 sample, #F7 sample, #F8 sample and #F9 sample prepared in Examples 5 to 9 of the present invention, use an ion sputtering instrument to prepare gold electrodes with a diameter of 2 mm on both sides, and test their dielectric properties and energy storage properties according to conventional detection methods. The specific results are as follows: Figure 12 to Figure 14 shown.
[0236] This experiment compares pure polymer PVDF-PMMA (Comparative Example 1 sample) and commercial film capacitor BOPP to determine the energy storage density U of PVDF-PMMA and commercial film capacitor BOPP. e .
[0237] pass Fig.12 , Fig.13 and Fig.14 It can be seen that the two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure as a high-entropy filler can significantly improve the dielectric properties and energy storage density of PVDF-PMMA film. The pinning effect of local polycrystalline distortion in the two-dimensional high-entropy ceramic nanosheet filler restricts the movement of long polymer chains, thereby establishing a stronger cross-linked network structure under the action of a strong electric field and reducing losses. In addition, the charge shielding layer around the interface between the two-dimensional high-entropy ceramic inorganic filler with a "core-shell" structure of the present invention and the organic polymer hinders the injection and transfer of space charges, which is beneficial to enhance the breakdown field strength E of the composite dielectric film material. b . In the range of the mass ratio of KNN material to PVDF-PMMA being 2.28% to 16.01% and the mass ratio of LNBCT high entropy material to PVDF-PMMA being 0.61% to 4.32%, the prepared composite dielectric film materials all exhibit excellent dielectric properties and energy storage performance. Preferably, for Example 8, when the mass ratio of KNN material to PVDF-PMMA is 11.61% and the mass ratio of LNBCT high entropy material to PVDF-PMMA is 2.90%, the highest energy storage density U is obtained under an applied electric field of 557.1 MV / m. e (22.54J / cm 3 ), which far exceeds the energy storage density U of pure polymer PVDF-PMMA e (6.49J / cm 3 ), and the energy storage density U of commercial film capacitor BOPP e (1.2J / cm 3 ). At this time, the charge and discharge efficiency η of the composite dielectric thin film material prepared by the present invention is 70.5%.
[0238] The preparation process of the present invention is simple, and the composition ratio of the materials is easy to optimize and adjust, thereby realizing the sheeting and high entropy of the raw materials. The dielectric energy storage properties of the prepared two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material KNN@LNBCT / PVDF-PMMA are improved, meeting the dielectric energy storage performance requirements of high dielectric energy storage capacitors. In addition, the composite dielectric film material has good reliability and toughness, and can be industrialized.
[0239] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material, characterized in that: The two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric film material includes an intermediate layer containing a KNN@LNBCT / PVDF-PMMA composite material and upper and lower layers containing PVDF-PMMA organic polymer materials; in the intermediate layer, the mass ratio of KNN to PVDF-PMMA is 2.28% to 16.01%, and the mass ratio of LNBCT to PVDF-PMMA is 0.61% to 4.32%.
2. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 1, characterized in that: The following steps are involved: S1. Preparation of two-dimensional nanosheet KNN Two-dimensional nanosheets KNN were prepared by hydrothermal method using niobium pentoxide, sodium hydroxide, potassium hydroxide and ethylene glycol as raw materials; S2. Preparation of two-dimensional high entropy ceramic nanosheets KNN@LNBCT A mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions was prepared using lanthanum acetate, sodium nitrate, barium nitrate, calcium nitrate, tetrabutyl titanate, anhydrous ethanol and acetic acid as raw materials. The two-dimensional nanosheet KNN was then mixed with the mixed solution to prepare a two-dimensional high-entropy ceramic nanosheet KNN@LNBCT with a "core-shell" structure through a "sol-gel method". S3. Preparation of two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film materials Using two-dimensional high-entropy ceramic nanosheets KNN@LNBCT, PVDF and PMMA as raw materials, the upper and lower layers containing PVDF-PMMA organic polymer materials and the middle layer containing KNN@LNBCT / PVDF-PMMA composite materials were prepared respectively. The two-dimensional high-entropy ceramic nanosheets / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA was prepared by layer-by-layer casting method.
3. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 2, characterized in that: In the step S1, the molar ratio of niobium pentoxide, sodium hydroxide and potassium hydroxide is 1:1:3.
5.
4. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 2, characterized in that: The specific process of preparing the two-dimensional high entropy ceramic nanosheet KNN@LNBCT in step S2 is: S21, dissolving tetrabutyl titanate in a mixture of ethanol and acetic acid, and then sequentially adding Ba(NO3)2 acetic acid solution, Ca(NO3)2 aqueous solution, La(Ac)3 aqueous solution and NaNO3 aqueous solution, stirring to obtain a mixed solution containing barium ions, calcium ions, lanthanum ions, sodium ions and titanium ions; the molar ratio of lanthanum ions, sodium ions, barium ions, calcium ions and titanium ions is 0.25:0.25:0.25:0.25:1; S22, adding the two-dimensional nanosheet KNN obtained in step S1 to the mixed solution obtained in step S22, and mixing them thoroughly to obtain a turbid solution; and adjusting the pH to 6-7 under stirring conditions to obtain a precursor sol containing KNN@LNBCT; S23, gelling the precursor sol containing KNN@LNBCT to obtain a gel, and then drying and calcining to obtain a two-dimensional high entropy ceramic nanosheet KNN@LNBCT.
5. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 4, characterized in that: In step S21, ethanol-acetic acid is prepared by mixing anhydrous ethanol and acetic acid in equal volumes; the stirring time is 0.5h to 2h; In step S22, the stirring time is 0.5h to 2h; In the step S23, gelation is performed by heating in a water bath at 50°C to 90°C; drying is performed at 50°C to 90°C for 10 hours to 24 hours, and then calcining is performed at 500°C to 900°C for 1 hour to 3 hours.
6. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 2, characterized in that: The specific process of preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material in step S3 is: S31, dispersing PVDF and PMMA in DMF solvent, stirring evenly to obtain suspension A, i.e., upper and lower layers containing PVDF-PMMA organic polymer material; S32, ultrasonically dispersing the two-dimensional high entropy ceramic nanosheets KNN@LNBCT in the suspension A, and stirring to obtain a suspension B, which is an intermediate layer containing the KNN@LNBCT / PVDF-PMMA composite material; S33, evenly coating the suspension A on a clean glass and drying; Suspension B and suspension A are then coated on suspension A in sequence and dried; the solvent is removed and quenched to obtain a two-dimensional high-entropy ceramic nanosheet / polymer composite dielectric thin film material KNN@LNBCT / PVDF-PMMA.
7. The method for preparing the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric thin film material according to claim 6, characterized in that: In the step S31, the mass volume ratio of PVDF, PMMA and DMF is 0.2 g:0.05 g:2.0 mL.
8. An application of the two-dimensional high entropy ceramic nanosheet / polymer composite dielectric film material as claimed in claim 1 in high dielectric energy storage capacitors.
Citation Information
Cited By
Barium titanate sub-nanosheet and polymer compounded dielectric energy storage film as well as preparation method and application thereof
CN121905709A